Inclusive search for squark and Gluino production in pp̄ collisions at s=1.96TeV - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; et al. (2009)
We report on a search for inclusive production of squarks and gluinos in pp̄ collisions at s=1.96TeV, in events with large missing transverse energy and multiple jets of hadrons in the final state. The study uses a CDF Run II data sample corresponding to 2fb-1 of integrated luminosity. The data are in good agreement with the standard model predictions, giving no evidence for any squark or gluino component. In an R-parity conserving minimal supergravity scenario with A0=0, μ<0, and tan β=5, 95 C.L. upper limits on the production cross sections in the range between 0.1 and 1 pb are obtained, depending on the squark and gluino masses considered. For gluino masses below 280GeV/c2, arbitrarily large squark masses are excluded at the 95 C.L., while for mass degenerate gluinos and squarks, masses below 392GeV/c2 are excluded at the 95 C.L. © 2009 The American Physical Society.